Differences in colorectal cancer surgery outcomes in Serbia: hospitals in organized colorectal cancer screening and other hospitals - Banković Lazarević, Dušica S. (PONS - medicinski časopis, 2021)
Introduction and objective: The aim of this study was to compare mortality of patients after colorectal cancer surgery between hospitals in Serbia, which performed organized colorectal cancer screening and those which did not.  Method: The database included all patients who underwent surgery for colorectal cancer after the introduction of organized colorectal cancer screening Program in Serbia, in 2014- 2015. The target group were patients 50-74 years-old in the colorectal screening program, and the data was compared to the age-matched group from hospitals which did not perform the program. Univariate logistic regression was used to determine the significance of the differences in the observed variables, and the predictors of mortality after colorectal cancer surgery.Results: The total of 3631 patients were included in this study. The majority of them were operated due to the rectal cancer 2111 (58%), while 1062 (29.2%) were operated due to the colon cancer. Postoperative survival was significantly better in the target group in organized screening program (p=0.000; OR=0.46; 95% CI 0.33-0.62).There was a significant difference between patients who underwent surgery for colorectal cancer localized in the left colon, compared to the patients with localization in the right colon (p
Keywords: colorectal cancer, colorectal cancer surgery, mortality, organized cancer screening